Analysis of Euphemisms and Dysphemisms Expressions in the Podcast “Pertemuan Bersejarah dr. Tirta dan dr. Gia” - Najmi Ali Mumtaz; Imam Baehaqie; Rustono Rustono (Haluan Sastra Budaya, 2026)
This study investigates the linguistic dichotomy in medical communication in the digital era, focusing on euphemism and dysphemism. The interaction between dr. Tirta Mandira Hudhi and dr. Gia Pratama's appearance on Raditya Dika's podcast serves as a unique sociolinguistic case study in which professional medical authority is negotiated through contrasting verbal styles. Drawing on Keith Allan and Kate Burridge's Theory of Taboo, the research employs a descriptive qualitative method with note-taking to analyze the transcript. The problem identified is the traditional taboo nature of medical discourse, encompassing disease, death, and professional failure, which must be reformulated for a diverse digital audience. Findings reveal that dr. Gia predominantly employs euphemistic strategies to “shield” and maintain professional “face” and interpersonal harmony, aligning with his “backstage energy.” Conversely, dr. Tirta utilizes dysphemistic language as a “weapon”, including profanity and harsh dialects, as a pedagogical instrument to shock and engage specific demographics. The analysis shows that these styles function as a “Yin and Yang” dialectic, where euphemism preserves institutional dignity while dysphemism achieves educational penetration through blunt realism. This synthesis suggests a paradigm shift in how medical expertise is presented to the public, blending clinical decorum with digital-native authenticity.